2001
DOI: 10.1063/1.1360196
|View full text |Cite
|
Sign up to set email alerts
|

Alkali metal cation-ligand affinities: Basis set superposition correction for the Gaussian protocols

Abstract: The effect of basis set superposition error ͑BSSE͒ on Gaussian-2 and Gaussian-3 calculated alkali metal cation-ligand affinities has been studied. For these systems, we found that the standard Boys-Bernadi full counterpoise ͑CP͒ method often leads to correction terms that are physically incorrect. This problem may be rectified by using the geometry corrected counterpoise ͑GCP͒ method. The relationship between CP, GCP corrections, and deformation energy is discussed. In order to yield good agreement with existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
69
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 22 publications
12
69
1
Order By: Relevance
“…In 1998, Remko et al [38] used the complete basis set extrapolation method (CBS-Q) developed by Petersson and coworkers [39] to study LCAs relative to proton and Mg 2+ affinities of a series of simple molecules. Siu et al [40] examined the G2 [31] and G3 [41] Gaussian protocols for predicting Li + , Na + , and K + binding affinities, recommending that geometry corrected counterpoise calculations be adopted for the LCAs.…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, Remko et al [38] used the complete basis set extrapolation method (CBS-Q) developed by Petersson and coworkers [39] to study LCAs relative to proton and Mg 2+ affinities of a series of simple molecules. Siu et al [40] examined the G2 [31] and G3 [41] Gaussian protocols for predicting Li + , Na + , and K + binding affinities, recommending that geometry corrected counterpoise calculations be adopted for the LCAs.…”
Section: Introductionmentioning
confidence: 99%
“…[7,10,24,26,27,32,33] In many instances, reliable theoretical results have been shown to provide a complementary/alternative route for obtaining and confirming alkali metal cation affinities. [9, 34±37] Also, theoretical findings on the most stable and low-lying binding modes/structures often provide new insights into the interpretation of experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…At the levels of theory used here, the relative energies of HAlF þ and AlFH þ are seen to be much closer than suggested by a G2 study of these two minima, which reported E rel ðHAlF þ Þ ¼ À7:8 kJ mol À1 . We would caution that unmodified G2 theory is prone to inaccuracy in the treatment of metal-containing molecular ions, particularly those also featuring fluorine [13,16,17].…”
Section: Resultsmentioning
confidence: 98%
“…The CP-dG2thaw method [13] is an elaboration of Chemical Physics Letters 380 (2003) 325-329 www.elsevier.com/locate/cplett the Gaussian-2 (G2) method [14], which aims to furnish highly accurate thermochemical data on small molecules and molecular ions. Modifications adopted in CP-dG2thaw, which address identified deficiencies of the G2 protocol in treatment of main-group-metal-containing species [15][16][17], include use of a counterpoise correction [18] (ÔCPÕ) for basis set superposition error [13,17], assignment of a (ÔthawedÕ) correlation space encompassing inner-valence metal-based electrons [15,16,19], and use of a partially decontracted (ÔdÕ) metal atom basis set [13,20]. The justification for, and a detailed description of, these refinements have been given elsewhere [13,20,21].…”
Section: Theoretical Methodsmentioning
confidence: 99%